2018
DOI: 10.3389/fimmu.2018.00800
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of Vγ9Vδ2 T-Cell Immunotherapy in Cancer

Abstract: Increasing immunological knowledge and advances in techniques lay the ground for more efficient and broader application of immunotherapies. gamma delta (γδ) T-cells possess multiple favorable anti-tumor characteristics, making them promising candidates to be used in cellular and combination therapies of cancer. They recognize malignant cells, infiltrate tumors, and depict strong cytotoxic and pro-inflammatory activity. Here, we focus on human Vγ9Vδ2 T-cells, the most abundant γδ T-cell subpopulation in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 235 publications
(305 reference statements)
0
136
0
Order By: Relevance
“…This is consistent with previous reports, showing that expanded Vd1 + T cells possess broad cytotoxic potential in solid tumors, including colon cancer. 119 Ex vivo expansion of cd T cells using zoledronate and IL-2 has also been trialled in a number of studies, improving disease progression but failing to achieve improved overall survival in a number of solid tumor types (renal cell carcinoma, lung cancer, hepatocellular carcinoma). Their ability to recognise a broad range of tumor signals through NK receptors and their TCR allows them to avoid some of the most potent immune evasion mechanisms available to tumors.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous reports, showing that expanded Vd1 + T cells possess broad cytotoxic potential in solid tumors, including colon cancer. 119 Ex vivo expansion of cd T cells using zoledronate and IL-2 has also been trialled in a number of studies, improving disease progression but failing to achieve improved overall survival in a number of solid tumor types (renal cell carcinoma, lung cancer, hepatocellular carcinoma). Their ability to recognise a broad range of tumor signals through NK receptors and their TCR allows them to avoid some of the most potent immune evasion mechanisms available to tumors.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…114 This provides a unique advantage for cd T cells over conventional ab T cells. 119,120 These early trials should be interpreted with caution as they were designed for assessing safety of cd T-cell products and not their efficacy. However, Vd1 + T cells have been poorly characterised in solid tumors.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quality of this activity can be associated to prevention or development of HAM/TSP . Interestingly, Sabouri et al . demonstrated that the expression of perforin in CD8 + T lymphocytes from HAM/TSP patients was reduced compared to cells from AC and uninfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…ciated to prevention or development of HAM/TSP 57,58. Interestingly, Sabouri et al59 demonstrated that the expression of perforin in CD8 + T lymphocytes from HAM/TSP patients was reduced compared to cells from AC and uninfected individuals. HTLV-1-specific CD8 + CTLs from HAM/TSP patients also showed significantly lower degranulation levels in comparison to AC, by a CD107a mobilization assay.…”
mentioning
confidence: 99%